2014
DOI: 10.1021/ja5095183
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for Selecting PEGylation Sites on Proteins for Higher Thermodynamic and Proteolytic Stability

Abstract: PEGylation of protein side chains has been used for more than 30 years to enhance the pharmacokinetic properties of protein drugs. However, there are no structure- or sequence-based guidelines for selecting sites that provide optimal PEG-based pharmacokinetic enhancement with minimal losses to biological activity. We hypothesize that globally optimal PEGylation sites are characterized by the ability of the PEG oligomer to increase protein conformational stability; however, the current understanding of how PEG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(106 citation statements)
references
References 122 publications
4
102
0
Order By: Relevance
“…Because the angle θ is correlated to PEG-based stabilization, which is in turn associated with enhanced resistance to proteolysis, we anticipate that θ will be useful for identifying Asn-PEGylation sites that provide optimal proteolytic protection to β-sheet proteins and protein drugs. However, Asn-PEG is not genetically encodable: Asn-PEGylated peptides and proteins can be prepared via solid-phase peptide synthesis [58] and/or native chemical ligation [59], but not via biological expression. It will be interesting to see whether the correlation between PEG-based stabilization and side-chain orientation relative to OH groups holds for PEGs incorporated site-specifically [60] via chemoselective reactions [61] with genetically encodable amino acids whose structures differ substantially from that of Asn.…”
Section: How Peg Enhances Protein Conformational Stabilitymentioning
confidence: 99%
“…Because the angle θ is correlated to PEG-based stabilization, which is in turn associated with enhanced resistance to proteolysis, we anticipate that θ will be useful for identifying Asn-PEGylation sites that provide optimal proteolytic protection to β-sheet proteins and protein drugs. However, Asn-PEG is not genetically encodable: Asn-PEGylated peptides and proteins can be prepared via solid-phase peptide synthesis [58] and/or native chemical ligation [59], but not via biological expression. It will be interesting to see whether the correlation between PEG-based stabilization and side-chain orientation relative to OH groups holds for PEGs incorporated site-specifically [60] via chemoselective reactions [61] with genetically encodable amino acids whose structures differ substantially from that of Asn.…”
Section: How Peg Enhances Protein Conformational Stabilitymentioning
confidence: 99%
“…Such linkers may be better able to disrupt the structure of water near the PEGylation site, leading to the entropically favorable local surface desolvation we identified previously for Asn-PEGylation WW. 10 We speculate that the Cys linkers in 2p-1 , 2p-2 , 2p-3 , and 2p-4 may be too flexible and that the PrF linker in 4p may be too far from the protein surface for optimal stabilization via this mechanism. Indeed, the substantially larger PEG-based stabilization observed for PrG-PEGylation relative to Aha-PEGylation and for Asn-PEGylation relative to Gln-PEGylation demonstrate that moving this rigid planar functional group even one atom further from the peptide backbone can prevent the pendant PEG from providing optimal stabilization, presumably because such longer side chains are not as close to the protein-bound water of the first solvation shell and are therefore less able to participate in the stabilizing desolvation described above.…”
Section: Resultsmentioning
confidence: 89%
“…However, its reliance on Asn-PEGylation presents a major logistical challenge: Asn-PEG is not genetically encodable. Asn-PEGylated peptides and proteins can be prepared via solid-phase peptide synthesis 10 and/or native chemical ligation, 11 but not via biological expression. An attractive potential alternative to Asn-PEGylation is to incorporate PEG site-specifically 5 via chemoselective reactions 12 with genetically encodable amino acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEG acts as a molecular crowding reagent that decreases water activity, decreases dielectric constant, and enhances the excluded volume effect [3]. Recently, it has been shown that the surface of a protein near the site of PEGylation is locally dehydrated [12]. Furthermore, PEG has been shown to interact specifically with the surface of a G-quartet by molecular modeling analysis [13].…”
Section: Archivos Dementioning
confidence: 99%